Age - Sex Structure of Aged Population in Thailand - Prasartkul, Pramote; Varangrat, Anchalee; Vapattanawong, Patama; Kanchanakitsakul, Madee (Journal of Population and Social Studies [JPSS], 2023)
See PDF